WOMEN'S LANGUAGE ANALYSIS IN THE WISH MOVIE - Nadiya, Nidy (Linguistics and Literature Journal, 2025)
The representation of gender in animated films significantly affects people's perceptions of the construction of linguistic identity. This study examines the features of women's language in the Wish movie (2023) through a sociolinguistic analysis framework based on Lakoff's theory of women's language and Creswell's qualitative methodology. This study uses a descriptive qualitative approach with a literature research design, analyzing the dialogue of Asha's female protagonist through objective sampling and thematic content analysis. These findings identified seven linguistic features that manifested in the protagonist's speech: lexical hedges appeared 32 times, intensifiers 12 times, tagged questions 6 times, superpolite forms 4 times, empty adjectives and hypercorrected grammar 2 times each. The analysis reveals the multidimensional function of these features, which simultaneously reflect the persistence of traditional gender norms and support the empowerment of protagonists through strategic contextual implementation. Lexical hedging serves as a politeness strategy rather than simply a marker of uncertainty, while tag questions serve a rhetorical purpose that challenges patriarchal authority. Intensifiers reinforce the emotional urgency for community advocacy and a very polite form of negotiating social hierarchies while maintaining agency. This research shows that contemporary Disney animation presents an ambivalence between the reproduction of patriarchal ideology and progressive attempts to construct complex and empowered female characters, which contribute new insights into gender-language relations in popular media representation.Keywords: female language features, gender representation, sociolinguistic analysis